Estimating the Stock/Portfolio Volatility and the Volatility of Volatility: A New Simple Method. (7th February 2016) - Alghalith, Moawia
Abstract : We devise a convenient way to estimate stochastic volatility and its volatility. Our method is applicable to both cross-sectional and time series data, and both high-frequency and low-frequency data. Moreover, this method, when applied to cross-sectional data (a collection of risky assets, portfolio), provides a great simplification in the sense that estimating the volatility of the portfolio does not require an estimation of a volatility matrix (the volatilities of the individual assets in the portfolio and their correlations). Furthermore, there is no need to generate volatility data.